2011
DOI: 10.1016/j.jmb.2011.09.039
|View full text |Cite
|
Sign up to set email alerts
|

The Rate of Polymerase Release upon Filling the Gap between Okazaki Fragments Is Inadequate to Support Cycling during Lagging Strand Synthesis

Abstract: Upon completion of synthesis of an Okazaki fragment, the lagging strand replicase must recycle to the next primer at the replication fork in under 0.1 second to sustain the physiological rate of DNA synthesis. We tested the collision model that posits that cycling is triggered by the polymerase encountering the 5′-end of the preceding Okazaki fragment. Probing with surface plasmon resonance, DNA polymerase III holoenzyme initiation complexes were formed on an immobilized gapped template. Initiation complexes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…However, if a new polymerase is used for the synthesis of almost every Okazaki fragment, as suggested by previous exchange observations (Geertsema et al, 2014), these pathways are not required. Supporting this line of reasoning, several studies have suggested that no specific protein factor exists for signaling (Kurth et al, 2013), and that collision events are orders of magnitude too slow to support efficient replication (Dohrmann et al, 2011). These findings suggest polymerase release is a stochastic event with many possible triggers.…”
Section: Lagging-strand Polymerases Remain Behind the Replisomementioning
confidence: 95%
See 1 more Smart Citation
“…However, if a new polymerase is used for the synthesis of almost every Okazaki fragment, as suggested by previous exchange observations (Geertsema et al, 2014), these pathways are not required. Supporting this line of reasoning, several studies have suggested that no specific protein factor exists for signaling (Kurth et al, 2013), and that collision events are orders of magnitude too slow to support efficient replication (Dohrmann et al, 2011). These findings suggest polymerase release is a stochastic event with many possible triggers.…”
Section: Lagging-strand Polymerases Remain Behind the Replisomementioning
confidence: 95%
“…Processive replication events reveal polymerases remaining on the lagging strand behind the replisome ( Figure 5B). Some polymerases remain bound on the lagging strand for very long times (minutes) consistent with stalling upon completion of Okazaki-fragment synthesis (Dohrmann et al, 2011;Huber et al, 1987). Examination of kymographs from 55 replication events reveals that polymerase emergence from the replication fork is four times more frequent than direct binding from solution to the lagging-strand ( Figure 5C & S10), and the mean spacing between polymerases is 3.8 ± 0.4 kb, consistent with most polymerases rapidly completing…”
Section: Lagging-strand Polymerases Remain Behind the Replisomementioning
confidence: 97%
“…In addition they have either a built-in 3 0 -5 0 exonuclease site, located at a distance from the polymerase active site, or an associated subunit with 3 0 -5 0 exonuclease activity (reviewed in Patel and Loeb 2001;Kunkel 2004;McHenry 2011). In either case, the distance from the polymerase site to the exonuclease site necessitates that at least three nucleotides of the double-stranded DNA are unwound to allow editing.…”
Section: Dnae/ Dnaqmentioning
confidence: 99%
“…As isolated directly from cells, it has an average composition close to (a1u) 2 -(t 2 gdd 0 cx)-(b 2 ) 2 (17 subunits), where a1u is the polymerase core discussed in more detail below, b 2 is the sliding clamp, and t 2 gdd 0 cx is the clamp loader complex that may contain two to three t and one to zero g subunits (McHenry 2011).…”
Section: Eubacteriamentioning
confidence: 99%
See 1 more Smart Citation